Evaluating internal accreditation quality in medical education: perspectives of students, faculties, and stakeholders at Adama Hospital Medical College, Adama, Ethiopia, 2024 - Arero, Godana; Amdeslasie, Faska; Mwesigwa, Cathy (Frontiers in Education, 2025)
BackgroundAccreditation is a critical process to ensure educational quality and standards in medical training institutions. Internal accreditation serves as a self-regulatory mechanism to evaluate institutional performance against predefined standards. This study aimed to assess the quality of internal accreditation among medical students at Adama Hospital Medical College, focusing on the alignment with national and international educational standards.MethodsA mixed-methods study design was employed, integrating quantitative and qualitative approaches. A structured questionnaire was administered to 320 medical students selected through stratified random sampling to collect quantitative data on their perceptions of accreditation quality. Qualitative data were gathered through focus group discussions (FGDs) and in-depth interviews (IDIs) with faculty members and students. Data analysis involved descriptive and inferential statistics for quantitative data and thematic analysis for qualitative findings.ResultsQuantitative findings showed that 80% of students rated the internal accreditation process as satisfactory, with notable strengths in curriculum alignment (85%) and faculty performance evaluation (82%). However, resource availability (60%) and student feedback mechanisms (58%) require improvement. Regression analysis indicated a significant positive correlation between accreditation quality and students’ academic satisfaction (p < 0.05). Standard 1 was rated Excellent (100%), while Standards 3, 4, 5, 6, and 8 scored Good (80%). Standards 2, 7, and 9 received Satisfactory (60%). Overall, the assessment revealed strong foundations and identified areas needing strategic improvement to ensure continued educational quality. Qualitative findings highlighted themes including transparency in the accreditation process, the relevance of training content, and stakeholder engagement. While students appreciated regular evaluations and feedback, they expressed concerns about insufficient laboratory resources and limited clinical practice opportunities. Faculty members emphasized the need for continuous capacity building and enhanced collaboration with accreditation bodies.